Personalized Cancer Medicine: Molecular Diagnostics, Predictive biomarkers, and Drug Resistance. Issue 3 (7th December 2012) - Gonzalez de Castro, D; Clarke, P A; Al‐Lazikani, B; Workman, P
<x xml:space="preserve">Abstract</x> The progressive elucidation of the molecular pathogenesis of cancer has fueled the rational development of targeted drugs for patient populations stratified by genetic characteristics. Here we discuss general challenges relating to molecular diagnostics and describe predictive biomarkers for personalized cancer medicine. We also highlight resistance mechanisms for epidermal growth factor receptor (EGFR) kinase inhibitors in lung cancer. We envisage a future requiring the use of longitudinal genome sequencing and other omics technologies alongside combinatorial treatment to overcome cellular and molecular heterogeneity and prevent resistance caused by clonal evolution. Clinical Pharmacology & Therapeutics (2013); 93 3, 252–259. doi:10.1038/clpt.2012.237